Case Report: Special recoveries from major mental illness in childhood: a case series - Monarch, Elena S.; Foss, Sean (Frontiers in Child and Adolescent Psychiatry, 2025)
Sudden-onset, unexplained, and treatment-resistant neuropsychiatric symptoms have been reported in numerous pediatric patients. Prior to the identification of neuroimmune conditions including PANS and PANDAS, children with these conditions were diagnosed with psychiatric and neurological conditions and offered conventional psychiatric and therapeutic care. As connections between the immune and nervous systems become clearer, alternate curative treatments have emerged. This case series presents three pediatric patients' treatment experiences with sudden-onset severe neuropsychiatric symptoms such as disabling anxiety, tics, eating restriction, or hallucinations, and their full recoveries following treatment of their underlying infections, inflammatory responses, and gastrointestinal dysbiosis. Treatments included antimicrobials, nutraceuticals, probiotics, and dietary changes. Converging lines of research highlight the importance of considering neuroinflammatory conditions in the differential diagnosis of children with treatment-resistant neuropsychiatric symptoms.